Hydrodynamic modeling of a reservoir used to supply water to Belem (Lake Agua Preta, Para, Brazil) - Santos, Maria Lourdes Souza; Saraiva, André Luis de Lima; Pereira, José Almir Rodrigues; Nogueira, Patrícia Façanha Rocha de S. M.; Silva, Alex Costa da (Acta Scientiarum. Technology, 2015)
Lake Agua Preta is used by the Sanitation Company of Para (Cosanpa) to supply water to the Belem Metropolitan Region. This study aims to use the Base System Modeling Program Environmental Hydrodynamics (Sisbahia) model to simulate seasonal hydrodynamic conditions in the lake and identify areas with the greatest silting. The model results revealed an identical distribution of the velocity module for each month of the year. However, at the outlet of the lake, a water channel variation speed of 0.28 - 0.32 m s-1 was observed. Furthermore, at the inlet of the lake, vortex silting tended to occur, as verified by bathymetry. Sedimentation mainly occurred during periods of low rainfall, which is when Cosanpa increases the inflow of water to maintain the reservoir level and this leads to an increase in sediments in suspension. With the model, it was possible to identify locations with higher rates of sedimentation, and in the future, such data can serve as an effective tool for managing this water resource. Â